2002
DOI: 10.1097/00006842-200203000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Hypercortisolemic Depression Is Associated With Increased Intra-Abdominal Fat

Abstract: Hypercortisolemic depressed patients suffer from resistance to insulin and increased visceral fat. The fact that hypercortisolemia reverses depression-related fat loss, particularly in the visceral area, might partially explain why major depression can be considered a risk factor for cardiovascular disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
115
3
5

Year Published

2003
2003
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 190 publications
(128 citation statements)
references
References 17 publications
5
115
3
5
Order By: Relevance
“…Most importantly, our study confirmed the hypothesis that when both depression and high cortisol levels are present, the odds of the metabolic syndrome is increased. This is consistent with a study by Weber-Hamann et al (2002), who found among 45 older women that hypercortisolemic depression was associated with increased visceral fat and a larger accumulation of visceral fat over time (Weber-Hamann et al, 2006). How can it be explained that hypercortisolemic depression in particular is associated with a higher prevalence of metabolic syndrome?…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Most importantly, our study confirmed the hypothesis that when both depression and high cortisol levels are present, the odds of the metabolic syndrome is increased. This is consistent with a study by Weber-Hamann et al (2002), who found among 45 older women that hypercortisolemic depression was associated with increased visceral fat and a larger accumulation of visceral fat over time (Weber-Hamann et al, 2006). How can it be explained that hypercortisolemic depression in particular is associated with a higher prevalence of metabolic syndrome?…”
Section: Discussionsupporting
confidence: 92%
“…Depression has been linked to metabolic abnormalities, such as abdominal obesity, high blood pressure and insulin resistance (Raikkonen et al, 1996;Raikkonen et al, 2001;Weber-Hamann et al, 2002). Several pathways for these links have been suggested.…”
Section: Introductionmentioning
confidence: 99%
“…Depression is associated with increased activity of the HPA axis and the sympathetic nervous system [24], resulting in increased cortisol release and increased release of the catecholamines epinephrine and norepinephrine. Cortisol is a stress hormone, which stimulates glucose production, increases lipolysis and circulating free fatty acids, decreases insulin secretion from beta cells and decreases sensitivity to insulin [24][25][26][27]. It is postulated that a chronically high cortisol level, which is a feature of about 50% of depressed patients, results in obesity, insulin resistance and type 2 diabetes [24,28,29].…”
Section: Discussionmentioning
confidence: 99%
“…It is postulated that a chronically high cortisol level, which is a feature of about 50% of depressed patients, results in obesity, insulin resistance and type 2 diabetes [24,28,29]. Some studies found evidence for this hypothesis [27,28]. Epinephrine generates responses in glucose and fat metabolism similar to those of cortisol [26], also possibly resulting in insulin resistance and type 2 diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Any association between depression and coronary events has to be mediated by physiological factors. It is most likely that differences in activation states of the hypothalamicpituitary-adrenal axis 40,41 or neuro-endocrine overstimulation of CRP or fibrinogen 2,42,43 might yield differences between depressed and non-depressed patients. However, in the present analysis, we did not control for them, as they may be involved as mediating pathways.…”
Section: Obesity and Depression K-h Ladwig Et Almentioning
confidence: 99%